An Investigation Of Karma Yoga In The Bhagavad Gita (Journal of Namibian Studies : History Politics Culture, 2023)
There are a number of doctrines in ancient Indian philosophy that are considered to be the foundation stones for a complete outlook on life that is expressed in the philosophy of karma. The Bhagavad Gita is perhaps the most beloved and enduring scripture in Indian tradition and one of the most important chapters of this scripture is the one titled 'law of karma'. According to this theory, every individual makes profits from what he does and suffers from what he does as a result of his actions. Karma yoga practise is mainly based on Niskam-karma, rather than simply renunciation Karma for the sake of renouncing it. It is necessary for us to let go of attachments and the fruits of our actions in order to become free. Therefore, it is our svadharma to perform action, and not to be concerned with the fruits or results of that action. Bhagavat Gita preaches Karma which should be regarded as natural, intrinsic to man's existence, and that every individual must work hard in order to achieve happiness.